Validation of a new portable metabolic system during an incremental running test - Diaz, V.; Benito, P. J.; Peinado, A. B.; Alvarez, M.; Martin, C.; Di Salvo, V.; Pigozzi, F.; Maffulli, N.; Calderon, F. J. (Journal of Sports Science & Medicine, 2008)
We tested a new portable metabolic system, the Jaeger Oxycon Mobile (OM) at a range of running speeds. Six subjects carried out, in random order, two incremental tests on a treadmill, one of them using the OM, and the other using the Jaeger Oxycon Pro (OP). There are systematic errors in the measurements of oxygen consumption (VO2) and respiratory exchange ratio (RER) with the OM. Production of CO2 (VCO2) tends to be overestimated by the OM, although the differences are not significant. Ventilation (VE) showed very similar values in both analyzers. Data of VO2 and RER were corrected with a regression equation which minimised the differences among the devices. The portable metabolic system OM makes systematic errors in measurements of VO2 and RER which can be adjusted with a regression analysis to obtain data comparable to those obtained by fixed systems.